2019
DOI: 10.3389/fphys.2019.00808
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Transporters in the Primary Gastrointestinal Tract of Pre-Feeding Mozambique Tilapia Larva

Abstract: Fish larvae differ greatly from the adult form in their morphology and organ functionality. The functionality of the gastrointestinal tract depends on the expression of various pumps, transporters, and channels responsible for feed digestion and nutrients absorption. During the larval period, the gastrointestinal tract develops from a simple closed tube, into its complex form with differentiated segments, crypts and villi, as found in the adult. In this study, we characterized the expression of three peptide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 63 publications
2
6
0
Order By: Relevance
“…In contrast, slc15a2a, compared to b-type paralog (but also compared to both slc15a1 types), shows a very low and constant mRNA expression levels along the GIT, suggesting a minor role in intestinal uptake of di-and tripeptides. Our data are in line with previous detections of slc15a2 in the intestine (Romano et al, 2006;Ostaszewska et al, 2018) and, in particular, in the distal intestinal segments, as reported in Nile tilapia (Huang et al, 2015), in juvenile turbot (Scophthalamus maximus) (Xu et al, 2016), and in Mozambique tilapia (Con et al, 2019), suggesting a downstream concerted integration of Pept2 with Pept1 in the functionality of gut physiology, in order to completely absorb di-and tripeptides from the intestinal lumen (Smith et al, 2013b;Bisesi et al, 2015). However, in contrast to zebrafish (Tian et al, 2015), 4 days of induced fasting did not seem to affect slc15a2 mRNA levels (for both types) in Atlantic salmon, except for a higher expression of the fasted group in AMG for slc15a2b, and this difference might be due to different teleost species studied (Cypriniformes vs. Salmoniformes family representatives).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, slc15a2a, compared to b-type paralog (but also compared to both slc15a1 types), shows a very low and constant mRNA expression levels along the GIT, suggesting a minor role in intestinal uptake of di-and tripeptides. Our data are in line with previous detections of slc15a2 in the intestine (Romano et al, 2006;Ostaszewska et al, 2018) and, in particular, in the distal intestinal segments, as reported in Nile tilapia (Huang et al, 2015), in juvenile turbot (Scophthalamus maximus) (Xu et al, 2016), and in Mozambique tilapia (Con et al, 2019), suggesting a downstream concerted integration of Pept2 with Pept1 in the functionality of gut physiology, in order to completely absorb di-and tripeptides from the intestinal lumen (Smith et al, 2013b;Bisesi et al, 2015). However, in contrast to zebrafish (Tian et al, 2015), 4 days of induced fasting did not seem to affect slc15a2 mRNA levels (for both types) in Atlantic salmon, except for a higher expression of the fasted group in AMG for slc15a2b, and this difference might be due to different teleost species studied (Cypriniformes vs. Salmoniformes family representatives).…”
Section: Discussionsupporting
confidence: 93%
“…In our analysis, the effects of fasting on the gene expression variation were not evaluated in the complete GIT but, rather, in specific gut compartments and thus identifying PC and MG as the most responsive compartments to fasting. Furthermore, for the first time in Atlantic salmon, slc15a1a is shown to respond to fasting with lowering mRNA expression levels, confirming the high flexibility of both transporters in the context of gut physiology and their ability to respond to different luminal conditions and signals, as previously shown in Mozambique tilapia (Con et al, 2019), in Nile tilapia (Hallali et al, 2018), and in European sea bass (Kokou et al, 2019). Based on correlation analysis, moreover, the slc15a1 expression in PC and AMG appeared to be associated with the residual digesta content of the MG, suggesting high sensitivity of the peptide transporter to external stimuli.…”
Section: Discussionsupporting
confidence: 79%
“…In fact, at least to our knowledge, the only study available in the literature that specifically compares pept1a ( scl15a1a ) and pept1b ( slc15a1b ) in pre-feeding stages larvae refers to the Mozambique tilapia ( Oreochromis mossambicus ) and is limited to the intestinal organ only. In this case, pept1a ( slc15a1a ) and pept1b ( slc15a1b ) temporal trend of expression in the intestine goes parallel from 3 to 14 dpf (for details, see Table 4, and literature therein [49]).…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, in the Atlantic salmon, the slc15a2a paralogue exhibits a widespread tissue distribution, in terms of the presence of mRNA, but it is most abundant in the brain and, notably, in the gills. The expression of a PepT2 in the brain, operating as a di/tripeptide uptake system, has been observed in mammals (Wada et al ., 2005; Biegel et al ., 2006; Kamal et al ., 2008; Keep & Smith, 2011; Smith et al ., 2013; Viennois et al ., 2018) as well as in teleost fish species, e.g., zebrafish (Romano et al ., 2006) and Mozambique tilapia (Con et al ., 2019). But, noteworthy, the identification of PepT2 mRNA transcripts in the gills opens to the hypothesis that a di/tripeptide transporter might also be operating in such an epithelial tissue moving di/tripeptides directly from the aquatic environment to the blood and/or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Larva (3-14 dpf) NA (Con et al, 2017;Chourasia et al, 2018;Con et al, 2019;Con et al, 2021) Adult Proximal, mid and distal intestine, kidney, muscle, liver, brain, pituitary, skin, stomach, spleen, heart, fat, gills, oesophagus…”
Section: Introductionmentioning
confidence: 99%